A Simple maxwell Based Model in Order to Represent the frequency-dependent viscosity measured by ultrasound - Franco, Ediguer E.; Adamowski, Julio C.; Higuti, Ricardo T.; Buiochi, Flávio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
A previous work showed that viscosity values measured high frequency by ultrasound agreed with the values at low frequency by the rotational viscometer when conditions are met, such as relatively low frequency viscosity. However, these conditions strongly reduce the range of the measurement cell. In order to obtain a measurement range and sensitivity high frequency must used, but it causes a frequency-dependent decrease on the viscosity values. This work introduces a new simple in order to represent this frequency-dependent behavior.model is based on the Maxwell model for viscoelastic , but using a variable parameter. This parameter has physical meaning because it represents the linear behavior the apparent elasticity measured along with the viscosity by .Automotive oils SAE 90 and SAE 250 at 22.5±0.5oC viscosities at low frequency of 0.6 and 6.7 Pa.s, respectively,tested in the range of 1-5 MHz. The model was used in to fit the obtained data using an algorithm of non-linear in Matlab. By including the viscosity at low frequency an unknown fitting parameter, it is possible to extrapolate its . Relative deviations between the values measured by the and extrapolated using the model for the SAE 90 and SAE 250 oils were 5.0% and 15.7%, respectively.©2008 IEEE.
Keywords: Fitting parameters; Frequency-dependent; High frequency; Linear behavior; Low frequency; Maxwell models; Measurement cell; Measurement range; Non-linear; Physical meanings; Relative deviations; Rotational viscometer; Variable parameters; Viscosity value; Acoustic waves; Extrapolation; MATLAB; Maxwell equations; Ultrasonics; Viscosity